Webinar Pengabdian Masyarakat: Sikap Penerimaan Orang Tua Terhadap Anak Kebutuhan Khusus - Richo Surya Pradana; Muhammad Elmi Utama; Christina Jumisari Dewi (STIKES Columbia Asia Medan, 2025)
Children born with physical or mental limitations certainly make parents sad and sometimes not ready to accept them for various reasons. The presence of children with special needs has the potential to be a source of stress or stressors, which is influenced by parental acceptance. This method is designed to achieve the stated goals by combining theoretical insights with practical applications. This webinar has a significant impact on webinar participants, especially parents who have children with special needs with the aim of equipping parents with knowledge and understanding so that they are expected to accept the presence of their children who have mental or physical limitations. The stages of parental acceptance of children with special needs in this study include (1) the rejection phase, starting from a feeling of disbelief that the doctor has given a verdict that the child is a child with special needs; (2) the anger phase, usually occurs when parents realize that the child's condition is undeniable; (3) the bargaining phase, where parents try to bargain for the condition that occurs in the child; (4) the depression phase, experiencing problems in daily life due to pressure after pressure that cannot be denied; (5) the acceptance phase, where parents wholeheartedly accept that they have a child with special needs.